Infecção por Mycobacterium leprae em menores de 15 anos contatos de casos de Hanseníase - Gomes, Luciane Cardoso (2016)
leprosy in people under 15 years of age indicates an early exposure to the causative agent of the disease. It is a high-potential disabling disorder that has been considered hyperendemic in the state of Mato Grosso. Contacts of patients diagnosed with leprosy constitute a high-risk population for infection and disease. Anti-NDO-LID and anti- PGL-I serological tests are ancillary tools for detecting individuals with the infection and at a higher risk of developing the disease. Objective: to analyze the Mycobacterium leprae infection in people under 15 years of age, contacts of leprosy cases, through anti-NID-LID and anti-PGL-I serological tests, in the city of Cuiabá-MT, from 2014 to 2016. Method: this is a cross-sectional study with 250 people under 15 years of age, where 50 were household contacts, 160 were neighborhood contacts and 40 were case-contacts. The information was obtained through notification/investigation records of the disorder, the Information System for Notifiable Diseases in Mato Grosso, interviews by means of a standardized instrument and collection of blood samples, from February to July 2016. In order to analyze data, we employed the following tests: Prevalence Ratio, Kolmogorov-Smirnov, Kruskal-Wallis one- way ANOVA, Spearman correlation coefficient and Poisson and Quantile regressions. Results: among the 250 individuals, 127 (50.8%) were male and 123 (49.2%) were female, with a mean age of 8.3 years. The proportion of anti-NDO-LID positivity in neighborhood contacts was 6.9%; in household contacts, it was 4%; and in contact-cases, it corresponded to 7.5%. The general prevalence of infection in the household and neighborhood contacts was 6.2% with anti-NDO-LID and 2.8% with anti-PGL-I. The western region of the city of Cuiabá showed a higher proportion of seropositivity in the household and neighborhood contacts, while the rural region showed a higher rate of detection of leprosy cases in the child population from 2014 to 2015. We detected a percentage of 1.9% of new cases among the 210 household and neighborhood contacts. As for the factors associated with the seropositivity of the anti-NDO-LID test in neighborhood contacts, we found the variables “race/color” and “number of people in the residence”. We found a positive correlation between the titration of anti-PGL-I antibodies and the variables “number of people aged less than 15 years in the residence” and “overnight time in the same house of a person with leprosy”. The serological tests used in the study showed a reasonable agreement among themselves. Conclusion: the rapid anti-NDO-LID test was more suitable for detecting infection in the investigated population, when compared to the anti-PGL-I. We found a higher percentage of contacts infected in the western region. The accomplishment of a screening with employment of clinical evaluation and serological tests has proved to be a useful strategy to control leprosy. The factors associated with the positive result of the rapid test and the variables correlated with the titration of anti-PGL-I antibodies are linked to sociodemographic and co-housing aspects.